Mechanically robust neuroprotective stent by sequential Mg ions release for ischemic stroke therapy - Hongkang Zhang; Yang Zhang; Lili Sheng; Xiaofeng Cao; Chuanjie Wu; Baoying Song; Yunong Shen; Zikai Xu; Ge Song; Hao Sun; Qing Liu; Xunming Ji; et al. (Nature Communications)
Abstract Most acute ischemic stroke patients with large vessel occlusion require stent implantation post-thrombectomy for complete recanalization, yet they exhibit a high rate of poor prognosis due to ischemia-reperfusion injury. Thus, combining reperfusion therapy with neuroprotective treatment offers significant advantages. This study introduces a novel Mg2+ eluting stent by incorporating neuroprotective MgSO4 particles into a PLCL (poly (l-lactide-co-ε-caprolactone)) substrate using 3D printing technology. A novel MgSO4-particle/Mg2+-ions combined-mechanical reinforcement mechanism was introduced. Subsequently, the neuroprotective efficacy of the stents was validated through oxygen-glucose deprivation/reoxygenation-injured neuron cells in vitro and via the transient middle cerebral artery occlusion rat model to emulate human brain ischemia/reperfusion injury in vivo. The staged-release of Mg2+ is supposed to provide sequential neuroprotection that aligns with the treatment window for acute ischemic stroke. This study marks the first development of biodegradable neuroprotective brain stents and presents an effective strategy to alleviate cerebral ischemia-reperfusion injury.